Spherical Skyrmion black holes as gravitational lenses - Fabrizio Canfora; Ernesto F. Eiroa; Carlos M. Sendra (European Physical Journal C: Particles and Fields, 2018)
Abstract In this article, we extend the strong deflection limit to calculate the deflection angle for a class of geometries which are asymptotically locally flat. In particular, we study the deflection of light in the surroundings of spherical black holes in Einstein–Skyrme theory. We find the deflection angle in this limit, from which we obtain the positions and the magnifications of the relativistic images. We compare our results with those corresponding to the Schwarzschild and the global monopole (Barriola–Vilenkin) spacetimes.